![image](https://tex.z-dn.net/?f=+%5Cfrac%7B15+%7B%7D%5E%7B2%7D+%7D%7Bx+-+5x+%7B%7D%5E%7B2%7D+%7D+%2B+%5Cfrac%7B3%7D%7Bx%7D+%3D+%5C%5C+%5Cfrac%7B15+%7B%7D%5E%7B2%7D+%7D%7Bx%281+-+5x%29%7D+%2B+%5Cfrac%7B3%7D%7Bx%7D+%3D+%5C%5C+x+%3C+%3E+0%2C2+%5C%5C+x+%3C+%3E+0+%5C%5C+%5Cfrac%7B225%7D%7Bx%281+-+5x%29%7D+%2B+%5Cfrac%7B3%281+-+5x%29%7D%7Bx%281+-+5x%29%7D+%3D+%5C%5C+%5Cfrac%7B225+%2B+3+-+15x%7D%7Bx%281+-+5x%29%7D+%3D+%5Cfrac%7B228+-+15x%7D%7Bx%281+-+5x%29%7D+%3D+%5C%5C+%5Cfrac%7B228+-+15x%7D%7Bx+-+5x+%7B%7D%5E%7B2%7D+%7D+)
0,2 \\ x < > 0 \\ \frac{225}{x(1 - 5x)} + \frac{3(1 - 5x)}{x(1 - 5x)} = \\ \frac{225 + 3 - 15x}{x(1 - 5x)} = \frac{228 - 15x}{x(1 - 5x)} = \\ \frac{228 - 15x}{x - 5x {}^{2} } " alt=" \frac{15 {}^{2} }{x - 5x {}^{2} } + \frac{3}{x} = \\ \frac{15 {}^{2} }{x(1 - 5x)} + \frac{3}{x} = \\ x < > 0,2 \\ x < > 0 \\ \frac{225}{x(1 - 5x)} + \frac{3(1 - 5x)}{x(1 - 5x)} = \\ \frac{225 + 3 - 15x}{x(1 - 5x)} = \frac{228 - 15x}{x(1 - 5x)} = \\ \frac{228 - 15x}{x - 5x {}^{2} } " align="absmiddle" class="latex-formula">